1990
DOI: 10.1039/p19900001179
|View full text |Cite
|
Sign up to set email alerts
|

A novel probe for free radicals featuring epoxide cleavage

Abstract: This paper describes the identification of carbon-arbon bond cleavage within a defined range of epoxides as being a reaction type which is specifically diagnostic of free radicals adjacent to the epoxide. The speed of the epoxide cleavage is greater than that of hex-5-enyl radical cyclisation, and hence the reaction is kinetically competent to act as a new and discriminating type of probe for free radicals in solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 10 publications
3
18
1
Order By: Relevance
“…MS; m/z (%): 134 (M þ , 4), 116 (7), 105 (11), 91 (100), 77 (7), 65 (30), 51 (9), 39 (11). MS data were also presented in [24], and 1 H and 13 C NMR (CDCl 3 ) spectra in [25].…”
Section: Benzyl Vinyl Ether (11)mentioning
confidence: 99%
“…MS; m/z (%): 134 (M þ , 4), 116 (7), 105 (11), 91 (100), 77 (7), 65 (30), 51 (9), 39 (11). MS data were also presented in [24], and 1 H and 13 C NMR (CDCl 3 ) spectra in [25].…”
Section: Benzyl Vinyl Ether (11)mentioning
confidence: 99%
“…Filtration and solvent removal in vacuo gave the crude product, which was purified by column chromatography (PE/EtOAc, 4:1) to yield the allylic alcohol 5a (62 mg, 63 %) as a viscous yellow oil (E:Z, 65:35) whose data was consistent to that reported. [51] (b) A solution of 4a (52 mg, 0.189 mmol, 1 equiv.) in dry DMSO (5 mL) was treated at 25°C with LiOtBu in THF (0.38 mL, 1.0 , 0.38 mmol, 2 equiv.).…”
Section: General Erbr Proceduresmentioning
confidence: 99%
“…Although in the most cases the C-O bond suffered homolysis, in certain studies homolytic rupture of C-C bond was proved and this was even suggested as a test on the formation of radical intermediates [122,123]. In [123] vinyl ether 141 was obtained by this procedure (Scheme 68).…”
Section: Methods and Mechanisms Of Epoxy Compounds Reductionmentioning
confidence: 99%